Microcomputer-based artificial vision support system for real-time image processing for camera-driven visual prostheses - Fink, Wolfgang; You, Cindy X; Tarbell, Mark A (Journal of Biomedical Optics, 2010)
It is difficult to predict exactly what blind subjects with camera-driven visual prostheses (e.g., retinal implants) can perceive. Thus, it is prudent to offer them a wide variety of image processing filters and the capability to engage these filters repeatedly in any user-defined order to enhance their visual perception. To attain true portability, we employ a commercial off-the-shelf battery-powered general purpose Linux microprocessor platform to create the microcomputer-based artificial vision support system ( AVS ) for real-time image processing. Truly standalone, AVS is smaller than a deck of playing cards, lightweight, fast, and equipped with USB, RS-232 and Ethernet interfaces. Image processing filters on AVS operate in a user-defined linear sequential-loop fashion, resulting in vastly reduced memory and CPU requirements during execution. AVS imports raw video frames from a USB or IP camera, performs image processing, and issues the processed data over an outbound Internet TCP/IP or RS-232 connection to the visual prosthesis system. Hence, AVS affords users of current and future visual prostheses independent mobility and the capability to customize the visual perception generated. Additionally, AVS can easily be reconfigured for other prosthetic systems. Testing of AVS with actual retinal implant carriers is envisioned in the near future.